Ethical leadership and role of in managing organizational change: Analytical study - Alsulami, Mofleh Hamed (Journal of Economic, Administrative and Legal Sciences, 2024)
The significance of the ethical dimension in organizations has become imperative, particularly following their call to monitor international indicators related to transparency and integrity. Implementing ethical behaviors and practices during organizational change management is essential for achieving strategic aspirations and meeting contemporary and future environmental requirements. This study explored ethical leadership and organizational change management, their essence, and their relationship through the proposed model. The researcher utilized a descriptive-analytical approach based on induction and comparison of the study's literature to accomplish the study's objectives. Consequently, several key findings were derived: Ethical leadership transforms the organization into a system characterized by adequate inputs, processes, outputs, and organizational climate. Ethical leadership can foster an organizational ethical culture that supports managing organizational change by balancing individual and organizational values. The proposed model focuses on ethical leadership and its role in guiding the attitudes and behaviors of employees in managing organizational change to achieve the desired performance and behavior. In light of these findings, the study recommended several measures, notably: Organizations should focus on implementing ethical standards and organizational values for leaders and employees through enacting systems, regulations, rules, and ethical codes of conduct. Ethical leaders should define the ethical standards and criteria through which they manage organizational change, and organizations should hold awareness and developmental programs for leaders and employees to equip them with skills and knowledge to achieve the desired organizational change.
Keywords: Ethical leadership; organizational change management; organizational change models; leadership; ethics